The Language Development in 3-Year-Old Children - Padli, Al; Marselina, Suci (The Future of Education Journal, 2025)
This study examines the language development of children aged 3-4 years. The purpose of this research is to understand how language development occurs in this age group. This study employs a qualitative descriptive approach, with the primary informants being the child’s immediate family members, including parents and siblings. Data were collected through observation, interviews, and documentation. The collected data were then analyzed using qualitative descriptive analysis techniques, including data reduction, data presentation, and drawing conclusions or verification. The results of the study indicate that language development in 3-year-old children encompasses five main aspects. First, the phonetic aspect, which refers to the sounds of language. Second, the morphological aspect, which involves changes in word forms and their relation to meaning and word groups. Third, the syntactic aspect, which concerns the arrangement of words including Subject, Predicate, Object, and Complement to form meaning. Fourth, the semantic aspect, focusing on the understanding of meaning in each word. Fifth, the pragmatic aspect, which involves the polite use of language in accordance with the context of the situation. Overall, almost all indicators of language development in 3-4-year-old children were achieved very well. Only in the pragmatic aspect did the child’s development reach an adequate or moderately developing stage. However, in general, the language ability of 3-4-year-old children can be categorized as excellent or meeting the expected developmental indicators.